2020
DOI: 10.1002/jcb.29607
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CRNDE is activated by SP1 and promotes osteosarcoma proliferation, invasion, and epithelial‐mesenchymal transition via Wnt/β‐catenin signaling pathway

Abstract: Long noncoding RNAs (lncRNAs) were identified as a vital part in the development and progression of cancer in recent years. Colorectal neoplasia differentially expressed (CRNDE), a lncRNA, functions as an oncogene in some malignant neoplasias, but its role in the progression of osteosarcoma (OS) is still poorly understood. To dissect the difference in the expression of CRNDE, quantitative real-time polymerase chain reaction was utilized to evaluate it in OS tissues and cell lines (U2OS, MG63, and MNNG/HOS) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…25 In triple negative breast cancer, LINC01123, activated by FOXC1, regulates cell growth through miR-663a/CMIP signaling. 6 In this study, we observed that the expression of LINC01123 was clearly upregulated in OS cell lines. Moreover, LINC01123 promoted cell proliferation, metastasis, and stemness in vitro.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…25 In triple negative breast cancer, LINC01123, activated by FOXC1, regulates cell growth through miR-663a/CMIP signaling. 6 In this study, we observed that the expression of LINC01123 was clearly upregulated in OS cell lines. Moreover, LINC01123 promoted cell proliferation, metastasis, and stemness in vitro.…”
Section: Discussionmentioning
confidence: 60%
“…8 Accumulating evidence indicates that LINC01123 promotes tumor growth in various cancers. 6,9 However, the function of LINC01123 in OS remains unknown.…”
mentioning
confidence: 99%
“…As expected, a strong relationship between several of these lncRNAs and mesenchymal transition in solid tumors had been reported in the literature. For example, mesenchymal transition was reinforced by CRNDE via the Wnt/β-catenin pathway in osteosarcoma [ 18 ], and lncRNA PVT1 sponged miR-195 to enhance EMT and induce therapeutic resistance in cervical cancer [ 19 ]. Therefore, we identified 149 lncRNAs that might play important roles in regulating mesenchymal transition.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it remains unknown how sorafenib elevates CRNDE level. Previous reports have shown that some factors such as RNA binding proteins, transcription factors, epigenetic modification, miRNAs, or specific signal pathways participate in the regulation of CRNDE ( Wang et al, 2015 ; Huan et al, 2017 ; Jiang et al, 2017 ; Kiang et al, 2017 ; Ding et al, 2020 ). Sorafinib may upregulate CRNDE through one or several above factors, or other mechanism(s).…”
Section: Discussionmentioning
confidence: 99%